Regional cooperation and health diplomacy in Africa: from intra-colonial exchanges to multilateral health institutions - Philip J. Havik (História, Ciências, Saúde: Manguinhos)
Abstract Tracing the pathways of cooperation in health in sub-Saharan Africa from hesitant exchanges to institutionalized dimensions from the 1920s to the early 1960s, this article addresses regional dynamics in health diplomacy which have so far been under-researched. The evolution thereof from early beginnings with the League of Nations Health Organization to the Commission for Technical Assistance South of the Sahara and the World Health Organization’s Regional Office for Africa, shows how bilateral dimensions were superseded by WHO’s multilateral model of regional cooperation in health. Alignments, divergences, and outcomes are explored with respect to the strategies and policies pursued by colonial powers and independent African states regarding inter-regional relations, and their implications for public health and epidemiological interventions.